(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to investigate the impact of Internet use on the academic achievement of Zliten College of Education students in the Statistics course. Specifically, this study attempted to answer the following questions: - What is the impact of Internet use on the academic achievement of Zliten College of Education students in the Statistics course? - What is the impact of the gender variable on the academic achievement of Zliten College of Education students using the Internet? - What is the impact of the interaction between the method of presenting the educational material and gender on the achievement of Zliten College of Education students in the Statistics course? The study sample consisted of (60) students, (30) of whom were male and (30) female. The study reached the following results: - There were statistically significant differences in the overall arithmetic mean on the achievement test in favor of the experimental group, meaning that the experimental group performed better than the control group. - There was a statistically significant difference in the overall arithmetic mean in favor of females. In academic achievement. - There was a statistically significant effect in favor of the interaction between the method of material presentation and gender. The researcher recommended conducting further studies on the use of the internet in education and the generalization of its use in distance learning